The Effectiveness of Flipping Book Media on Adolescents’ Knowledge and Attitudes Towards Premarital Sex - Wulan Juniarti; Ragil Setiyabudi; Suci Ratna Estria (HealthCare Nursing Journal, 2026)
Sexual education remains a sensitive topic in Indonesian society despite the increasing rates of unwanted pregnancies and sexually transmitted infections among adolescents. In 2024, the Ministry of Health Indonesia recorded 35,415 new HIV cases and 12,481 new AIDS cases. According to WHO (2025), unintended pregnancies among girls aged 15–19 often result in unsafe abortions, especially in low- and middle-income countries. This study aimed to determine the effect of sexual education using flipping book media on adolescents’ knowledge and attitudes toward premarital sex at SMK Muhammadiyah Larangan. A quantitative pre-experimental one-group pretest-posttest design was employed involving 90 students selected through stratified random sampling. Data were analyzed using the Wilcoxon signed-rank test due to non-normal distribution. The results showed significant differences in both knowledge (p = 0.01) and attitude (p = 0.01) before and after the intervention, indicating that sexual education using flipping book media effectively improves adolescents’ knowledge and attitudes regarding premarital sex.